PENGARUH RESIDUAL INCOME DAN MARKET TO BOOK RATIO TERHADAP STOCK RETURN PADA INDUSTRI MANUFAKTUR - Andian Ari Istiningrum; Suryati Suryati Suryati (Universitas Negeri Yogyakarta, 2014)
The aims of this research are to determine the influence of residual income and market to book ratio toward stock return in the manufacture companies listed in the Bursa Efek Indomesia (BEI) during 2010-2012. The number of population is 135 manufacture companies and 30 manufacture companies based on the criterions are chosen as the research sample. Historical data from 2010 to 2012 is used in this research. Data is analyzed by multiple regression. The research reveals that residual income and market to book ratio individually has a positive and significant influence toward stock return. Market to book ratio is proven as the factor that provides higher influence as compared to residual income.